2009
DOI: 10.1292/jvms.71.9
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Vertebral Heart Score in Coughing Dogs with Chronic Degenerative Mitral Valve Disease

Abstract: ABSTRACT. The objective of the present study was to evaluate the usefulness of the vertebral heart score (VHS) in coughing dogs with chronic degenerative mitral valve disease (MVD). Survey thoracic radiographs of 90 dogs with a history of cough and clinical and echocardiographic evidence of MVD were evaluated by 2 independent observers. The observers were asked to first determine the origin of the cough as cardiac, non-cardiac or mixed and then to measure the VHS. Agreement regarding diagnosis of the origin of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
32
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 24 publications
4
32
0
Order By: Relevance
“…Left atrial size represents another potentially important cofactor for the presence of coughing in dogs affected by MMVD, and this is supported by the increased risk in dogs with increased LA size, observed on thoracic radiography or echocardiography. This finding supports previous observations that bigger than normal hearts can exert a mechanical dorsal pressure on the airways with subsequent stimulation of coughing receptors . Such pressure, however, may not be the primary cause of bronchial collapse, as indicated in a study in which the association between LA enlargement and airway collapse was not confirmed in dogs with MMVD …”
Section: Discussionsupporting
confidence: 90%
“…Left atrial size represents another potentially important cofactor for the presence of coughing in dogs affected by MMVD, and this is supported by the increased risk in dogs with increased LA size, observed on thoracic radiography or echocardiography. This finding supports previous observations that bigger than normal hearts can exert a mechanical dorsal pressure on the airways with subsequent stimulation of coughing receptors . Such pressure, however, may not be the primary cause of bronchial collapse, as indicated in a study in which the association between LA enlargement and airway collapse was not confirmed in dogs with MMVD …”
Section: Discussionsupporting
confidence: 90%
“…Although the area under the ROC (AUROC) curve or plot is the best summary of the accuracy of a diagnostic test, and AUROC can be used to compare tests done on the same or similar patient groups, it cannot directly be used to determine the effect of a test result on the individual patient . Vertebral heart scale (VHS) as a measurement of heart size discriminated between CHF and noncardiac causes of coughing in dogs with MR, with an AUROC of 0.92 . A value of 1.0 is a perfect test and 0.5 is no better than chance.…”
mentioning
confidence: 99%
“…11 Vertebral heart scale (VHS) as a measurement of heart size discriminated between CHF and noncardiac causes of coughing in dogs with MR, with an AUROC of 0.92. 12 A value of 1.0 is a perfect test and 0.5 is no better than chance. A diagnostic test should be done when the pretest probability of the condition being present is between thresholds for treating the disease in question or ruling out the condition.…”
mentioning
confidence: 99%
“…While puppy VHS does not change [9], kitten VHS decreases with growth [1]. Furthermore, VHS is known to be increased in coughing dogs compared with non-coughing dogs [2]. In non human primates, only one report has described VHS in the common marmoset (9.42  0.44v) [10].…”
mentioning
confidence: 99%
“…VHS has proven useful as an easily measured and relatively objective value [3]. In dogs, studies of VHS in puppies, adult dogs and different breeds have been performed [2][3][4][5]9]. Less research into VHS has been performed for cats than for dogs, although studies comparing kittens and adult cats have been reported [1,6].…”
mentioning
confidence: 99%